The Influence Of Family Support In Exclusive Breastfeeding On Breastfeeding Self-Efficacy Status In Postpartum Mothers - Hasri Yulianti; Ignasensia Dua Mirong; Diyan Maria Kristin (Jurnal Health Sains, 2023)
Background: Breast milk is the natural first food given to babies, providing all the energy and nutrition needed by babies aged 0 to 6 months. Babies who receive exclusive breast milk are babies who only receive breast milk without providing complementary foods. Coverage of babies receiving exclusive breast milk in 2020 is 66.06%. There are two provinces that have not achieved the 2020 Strategic Plan target, namely Maluku and West Papua. Meanwhile, for the East Nusa Tenggara region, the coverage of babies receiving exclusive breastfeeding is 74.5%. Objective: to determine the effect of family support in providing exclusive breastfeeding on breastfeeding self-efficacy in postpartum mothers. Research method: quantitative research type with analytical survey using a cross sectional approach with purposive sampling technique with a total sample of 88. Data analysis using statistical methods Chi square. Research results: obtained values p 0.000 < α (0.05), then there is a significant influence between family support in providing exclusive breastfeeding on breastfeeding self-efficacy status. Conclusion: there is a significant influence between family support in providing exclusive breastfeeding on breastfeeding self-efficacy status. Family support is the most important element in helping individuals solve a problem. If there is support, self-confidence will increase